Negative affectivity and eating behavior: Differential relationships between young and middle-aged adults - Libertad Paredes-Díaz; Yolanda Campos-Uscanga (Indian Journal of Psychiatry)
Background: Chronic stress is a well-established factor influencing unhealthy eating behaviors. Anxiety has been linked to emotional eating and acts as a mediator between depression and body mass index. However, the interaction between negative affectivity and eating behavior may vary across different life stages, suggesting that these relationships could differ between age groups. Aim: The study aimed to explore whether the relationship between negative affective states and eating behavior differs between young adults and middle-aged adults. Materials and Methods: A cross-sectional study was conducted among 172 participants: 87 young adults and 85 middle-aged adults. Sociodemographic data were collected, and participants completed the Depression Anxiety Stress Scales (DASS-21), Adult Eating Behavior Questionnaire, Spanish version (AEBQ-Esp), and the Emotional Eating Scale. Results: Young adults exhibited significantly higher levels of negative affectivity compared to middle-aged adults (d = 0.39), although differences in eating behavior were only observed in the dimension of eating slowness (d = -0.37). A negative correlation was found between negative affectivity and the family dimension of emotional eating in young adults (r = -0.332), while a positive correlation emerged in middle-aged adults (r = 0.259). The analysis by age groups revealed distinct patterns of association between stress and dimensions of eating behavior and emotional eating, with stress showing the most robust associations. Conclusions: The findings indicate that, while negative affective states are associated with emotional eating in both age groups, the nature of these associations varies significantly. In some cases, the same factor may serve as a risk factor in one age group and a protective factor in another.